DFT Study of Carbon Crystals from Nested K4 Lattice to BC‐8 Structure. Issue 6 (22nd February 2016) - Hagita, Katsumi; Sahara, Ryoji; Kawazoe, Yoshiyuki
Abstract: Carbon crystals of a nested K4 lattice and BC‐8 structure are studied. We propose a unified relationship between the nested K4 lattice and the BC‐8 structure. The atomic positons of both structures can be given by Wyckoff position 16(c) of space group No. 206 and its shifted lattice. We can obtain continuously changing configurations from the nested K4 lattice to the BC‐8 structure with one parameter. DFT calculation based on plane waves is performed in order to estimate the total energy and phonon DOS. The structure near the BC‐8 structure is found to have a stable state. We consider the nested K4 lattice a saddle point on the energy landscape and it is in a metastable state. Abstract : We propose a relationship between a nested K4 lattice and the BC‐8 structure on the basis of Wyckoff position 16(c) of space group No. 206. The continuous change in configurations from the nested K4 lattice to the BC‐8 structure can be written with one parameter. The stability of these structures is studied by estimating the total energy and the phonon DOS.